The role of the protein PGR5 in photoprotection and photosynthetic productivity in rice (Oryza sativa L.) - Ajigboye, Olubukola Omowunmi (2013)
In plants, the need to efficiently respond to constant environmental fluctuations has led to the evolution of photoprotective mechanisms to regulate photosynthetic light reactions. One of such mechanism is cyclic electron transport (CET) which generates a pH gradient inducing the nonphotochemical quenching (NPQ) of excess excitation energy, synthesis of ATP and maintenance of balanced redox state of the photosynthetic electron transport (PET) chain. Two major pathways of CET involve the NADH dehydrogenase-like complex (NDH)-dependent pathway, and the Proton Gradient Regulation 5 (PGRS)-dependent pathway. However, the mechanism and function of the PGRS-dependent CET to adapt the photosynthetic process in response to environmental variations and its impact in rice photosynthesis remains unclear. This study aims to determine the role of the photo protective protein, PGRS in the regulation of photoprotection and photosynthesis under constant as well as dynamic conditions and its impact on plant growth and development. Oryza sativa var. Kaybonnet, PGRS RNA interference (RNAi) and overexpression (OE) transgenic rice plants were characterised based on their physiological and morphological traits in a controlled environment and in glasshouse under constant and fluctuating light intensities. This study showed that PGRS-dependent CET was actively occurring in rice leaves grown under non saturating light but its rate increased significantly with overexpression of the PGRS protein in saturating light. Under constant and fluctuating light, elevated NPQ observed in the OE was absent in the RNAi lines indicating that PGRS is essential for cyclic electron flow in rice both during induction and at steady state photosynthesis. CO2 assimilation in both OE and RNAi were limited by maximum rate of carboxylation (Vcmax) although the RNAi was also photoinhibited. Experiments under dynamic condition of low atmospheric moisture indicated that the PGRS-dependent CET plays an important role in photoprotection of PSI and PSI!. Results from this experiment further suggest that PGRS could function efficiently in stress alleviation both in the short- and long term. Growth and biomass accumulation in the glasshouse and controlled environment showed that the PGRS protein is important in rice leaf photosynthesis. However, in a biomass experiment, significant photosynthetic advantage attributed to overexpression of PGRS could not be identified except in photoprotection and regulation of the PET chain. This study indicates that the ATP/NADPH ratio may modulate PGRS dependent CET response in rice, however, its regulation is likely to depend on the availability of PSI electron acceptors such as ferredoxin. PGRS may be important in meeting the demand for ATP in rice. In conclusion, this study has shown that the protein PGRS plays a very important role in enhancing photoprotection and is required for efficient photosynthesis in rice. However, there may be need for balance between enhancing photo protection and crop productivity in future improvement programmes.